Grasping and Shaping the Emergence of GenAI in Education: Insights from a Workshop Series with Practitioners - Otto, Sofie; Ejsing-Duun, Stine; Bertel, Lykke Brogaard (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
This practice paper reports on the iterative development, facilitation, and refinement of a workshop series with STEM educators centering on the role of Generative Artificial Intelligence (GenAI) in active and student- centered teaching and learning practices. A tentative deck of design lenses representing various types of GenAI interactions served as a point of departure for activating and inspiring dialogue and co-creation of teaching and learning designs that consider the role of GenAI-powered tools based on local contexts. We present key themes and ideas emerging from these dialogues and outline the iterative refinement of the design lens deck for future use in educational practice – in dialogue with both educators and students.